Chemotherapy in locoregionally advanced nasopharyngeal carcinoma-a review - Krstevska, Valentina; Stojkovski, Igor (My University, 2008)
Locoregionally advanced nasopharyngeal carcinoma (NPC), when traditionally treated with radiotherapy (RT) alone, has been associated with low overall survival (OS). Efforts to improve the efficacy of treatment for locoregionally advanced NPC have led to the use of multimodality approach with combination of RT and chemotherapy (CT). Analyzing the historical progress of the incorporation of CT as an integral part of the management of advanced NPC, we reviewed 12 randomized controlled trials on induction, concurrent, and adjuvant therapy, or a combination of these approaches. Four meta-analyses on this subject have been also reviewed. Evidence that concurrent chemoradiotherapy (CCRT) provides significant improvement in OS in patients with locoregionally advanced NPC is based on the results of 2 meta-analyses and several randomized studies on the administration of CT concomitantly with RT. The revealed survival benefits with CCRT compared with RT alone resulted in confirmation of CCRT as the currently recommended treatment for patients with advanced-stage NPC. The recognition of the development of distant metastatic disease as more frequent pattern of failure when concurrent CT is utilized has led to the assumption that the use of both induction chemotherapy (ICT) and CCRT in a sequential manner may provide improvement in overall treatment outcome in this patient category. The definition of the precise role of sequential CT in the management of patients with locally advanced NPC is to be revealed from the results of future phase III trials addressing this issue.
Keywords: nasopharyngeal carcinoma; Chemotherapy